Coumarin và acridon alkaloid từ rễ cây Xáo tam phân (Paramignya trimera) - Dương, Trịnh Hoàng; Phương, Trần Thu; Ly, Hà Diệu; Vy, Nguyễn Thụy; Sơn, Đặng Văn; Hoa, Nguyễn Diệu Liên (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 4, 2016)
Abstract: